Reliability assessment method for environmental vibrations of a tunnel embedded in layered foundation. Issue 1 (May 2021) - Xu, Yonggang; Guo, Huiji; Di, Honggui
Abstract: This paper proposes a reliability assessment method for environmental vibrations of a tunnel embedded in layered foundation under moving train load. Based on wave functions transformation, a vehicle-track-tunnel-soil model for evaluating system dynamic response can be established. Then combined with the Monte Carlo simulation, the reliability assessment of environmental vibrations is realized. The effect of soil parameter uncertainty on the prediction result of environmental vibrations is analyzed via case studies. The results show that the predictions from the deterministic model tend to be conservative, which is less than the superior limit of 95% confidence interval of the uncertainty model predicted outcome. The soil parameter uncertainty has less influence on the distribution of system dynamic response, which mainly affects the system dynamic response amplitude.